Doing expertise multilingually and multimodally in online English teaching videos. (November 2020) - Ho, Wing Yee Jenifer; Tai, Kevin W.H.
Abstract: The use of online videos as a teaching resource is gaining importance. It opens up opportunities for the creation of knowledge, as educational content can now be accessed by anyone with an Internet connection. This democratisation of access to knowledge can also be seen in the language learning context, where English language teachers create online videos for a transnational audience. In this paper, we present a case study of how two online English teachers 'do expertise' in their lessons, drawing on their multilingual and multimodal repertoire so that expertise is talked into being. We conducted semi-structured interviews and analysed them by interpretative phenomenological analysis (IPA) to make sense of the teachers' experiences of designing online teaching materials, and how their expertise was talked into being in the process. The aim of this paper is to contribute to understanding of expertise in the context of online language teaching. We argue that online teachers 'do expertise' by drawing on their multimodal design knowledge, pedagogical knowledge and linguistic knowledge.